POPULATION DYNAMICS OF MYZUS PERSICAE (SULZER) (HEMIPTERA: APHIDIDAE) ON THREE HORTICULTURAL HOSTS (Acta Entomológica Chilena, 2022)
The main vital statistics of Myzus persicae (Sulzer) on three horticultura! species: Gallega lettuce, Ditmarchcabagge and Oliver Brussels sprout, were obtained. Aphids were reared under laboratory conditionsat 20 ± 1°C, 14:10 hours of photoperiod and a relative humidity of 60-70%. Two cohorts were used pereach horticultural species.Daily record of change of stage, number of dead individuáis and births was kept once adult stage wasreached. Net reproductive rate (R0) appeared 4,2 times higher in Brussels sprout Oliver variety than in Galicianlettuce and 1,3 times higher than in cabbage Ditmarch var. Intrinsic growth rate (rm) was significantlydifferent among the three horticultural species. The aphid showed a higher capacity of survival and reproductionon crucifer than lettuce.
Keywords: Myzus persicae, population dynamics, Gallega lettuce, Ditmarch cabagge, Oliver Brussels